Território, política e infraestruturas: a influência do governo federal na política urbana dos municípios brasileiros - Gallo, Fabrício [UNESP] (Universidade Federal de Uberlândia, Instituto de Geografia, Programa de Pós-Graduação em Geografia, 2013)
The evolution of Brazilian federalism (result of the influence and power of oligarchic elites, the different constitutional texts made and policies designed to collect taxes) shows one of the forms of how the Brazilian government uses the territory to effect the exercise of power. In the country, this use takes place by the imposition of rules that regulate and create tension among the entities, and mechanisms of distribution and redistribution of resources among federal agencies acquire great importance because they allow a bigger or lesser autonomy in public administration. The text aims to analyze the voluntary transfers of resources from the Federal Government to the municipalities. These Covenants act as a mechanism that can be configured in promoter of new selectivity and hierarchies between places. With the aim to understand the materialization of public resources in the territory, our analysis intends to identify how the Brazilian government makes use of constitutional mechanisms to enlarge and improve the urban infrastructure in the municipal scale.

A evolução do federalismo brasileiro (fruto da influência e do poder das elites oligárquicas, dos diferentes textos constitucionais elaborados e das políticas de arrecadação de impostos) aponta uma das formas de como o Estado brasileiro usa o território para efetivar o exercício do poder. No país, este uso se realiza por meio da imposição de normas que regulam e geram tensões entre os entes, sendo que os mecanismos de distribuição e de redistribuição de recursos entre os entes federados adquirem grande importância por permitirem uma maior ou menor autonomia na administração pública. O texto objetiva analisar como tomam forma os convênios do Governo Federal para os municípios brasileiros. Tais convênios funcionam como um mecanismo que pode se configurar em promotor de novas seletividades e hierarquias entre os lugares. Com o intuito de compreender a materialização dos recursos públicos no território, nossa análise busca apontar como o Estado brasileiro faz uso de mecanismos constitucionais para ampliar e melhorar as infraestruturas urbanas na escala municipal.
Territory, politics and infrastructures: the influence of the federal government in urban policy of the Brazilian municipalities
Keywords: território usado; desigualdade socioespacial; federação brasileira; políticas públicas; used territory; sociospatial inequality; Brazilian federation; public policies